Modelling Consumers’ Green Purchase Propensity with Perception, Cognition and Emotion in the Context of Sustainable Development - Babu, Simran; Dykha, Mariia; Abuselidze, George; Sahoo, Saroj Kumar; Proskurovych, Oksana; Mantalyuk, Olha; Ivanov, Maksym (European Journal of Sustainable Development, 2025)
Purchase propensity, an essential precursor to purchase behavior, is often overlooked by researchers, although it is a multifaceted phenomenon and is poorly investigated in the environmental context due to the role of psychological factors. The primary aim of this research is to explore the causal relationship between consumers’ propensity to purchase green products with their key psychological dimensions, such as perception, cognitive load, and emotion towards green products and thereby proposing relevant strategies for retail organisations to strengthen consumers’ purchase propensity towards the said products. To establish a strong theoretical basis for analysis, a thorough review of existing literature was conducted and was further supplemented by discussions with relevant researchers and experts in this domain. To facilitate a comprehensive understanding of the phenomenon, this study adopts a descriptive research design, enabling systematic observation and relationships within the above-mentioned context. Major findings of this conceptual article indicate that customers’ positive perception of green products will evoke emotional engagement with these products, and their cognitive load will be managed, ultimately increasing their propensity to purchase the said products. Drawing on sustainability literature, the directional relationships of the identified dimensions form a new model, which advances the understanding of how affective and cognitive mechanisms interact in green consumer behavior. This study provides a roadmap for marketers to integrate green concerns for consumerism by leveraging cognitive and emotional understandings. At a broader level, its social relevance is underlined by the term “green”, which provides a foundational framework for advancing sustainability goals and promoting eco-conscious consumer behavior for society and the globe at large. Keywords: perception, cognition, emotions, propensity, green products, ecological purchase, sustainable development, environment, model, structural relationships